2017
DOI: 10.1080/15548627.2017.1291471
|View full text |Cite
|
Sign up to set email alerts
|

SGPL1 (sphingosine phosphate lyase 1) modulates neuronal autophagy via phosphatidylethanolamine production

Abstract: Macroautophagy/autophagy defects have been identified as critical factors underlying the pathogenesis of neurodegenerative diseases. The roles of the bioactive signaling lipid sphingosine-1-phosphate (S1P) and its catabolic enzyme SGPL1/SPL (sphingosine phosphate lyase 1) in autophagy are increasingly recognized. Here we provide in vitro and in vivo evidence for a previously unidentified route through which SGPL1 modulates autophagy in neurons. SGPL1 cleaves S1P into ethanolamine phosphate, which is directed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 44 publications
4
78
0
Order By: Relevance
“…Sphingolipids are pleiotropic signaling molecules and we have earlier shown that S1P is neurotoxic (Hagen et al, ) and that systemic knock out of SGPL1 that catalyzes the breakdown of S1P can cause neurodegeneration (Hagen et al, ). Further, with SGPL1 fl/fl/Nes mice, we have demonstrated autophagy defects that could, in turn, lead to accumulation of aggregate‐prone proteins and behavioral changes in mice (Mitroi et al, ).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Sphingolipids are pleiotropic signaling molecules and we have earlier shown that S1P is neurotoxic (Hagen et al, ) and that systemic knock out of SGPL1 that catalyzes the breakdown of S1P can cause neurodegeneration (Hagen et al, ). Further, with SGPL1 fl/fl/Nes mice, we have demonstrated autophagy defects that could, in turn, lead to accumulation of aggregate‐prone proteins and behavioral changes in mice (Mitroi et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, in neurons SGPL1 deficiency causes accumulation of S1P on the one hand and a drop in phosphatidylethanolamine on the other hand. The latter proved to block neuronal autophagy flux via an mTOR independent mechanism (Mitroi et al, ), whereas the former was shown to stimulate neuronal autophagy (Moruno Manchon et al, )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, subsequent reductions in S1P levels may be implicated, although increased rather than decreased intracellular S1P have been associated with triggering autophagy (22). The pro-autophagic effect of S1P production and the importance of the subcellular localization of S1P accumulation have been recently described in neuronal cells (23)(24)(25). This body of work suggests that the autophagy triggered by ASM inhibition, which was associated with decreased S1P levels occurs via a different mechanism than by S1P overproduction.…”
Section: Discussionmentioning
confidence: 98%